Enhancing Self-Assessment Skills in Teacher Education Students’ Engagement - Margeviča-Grinberga, Ieva (Pedagogika, 2025)
This study examines the role of self-evaluation in teacher education, focusing on the engagement of 131 students in formative self-evaluation practices and their understanding of the process. A qualitative research design was used to assess the application of self-evaluation among students. The research was centred on students’ self-evaluation of their research projects presented in class and as course papers. These findings showed that self-evaluation can be useful when preparing a research project, potential amendments, and transformations.